Interior of Anglican Cathedral of St. John the Baptist - Squires, Allen; Squires, Pearl (1962)
Photograph of interior of Anglican Cathedral of St. John the Baptist. Identified by Pearl Squires on slide label as “St. Peter's Cathedral St. John's, NFLD.” Dark picture.